Role of FNAC in evaluation of Parotid Gland Swelling (Journal of Surgical Sciences, 2019)
Objectives: To find out the histological types of parotid neoplasm and to correlate thefindings of FNAC and final histological report in parotid gland neoplasm.Methods: A total 30 cases were studied from the inpatient departments of General Surgeryand Otolaryngology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka sinceJuly, 2011 to April, 2013. Fine Needle Aspiration Cytology (FNAC) was done in all cases andcompared with histopathology finding of postoperative specimen.Result: Regarding sex distribution benign neoplasm in female 13 (56.52%) and in male10(43.47%). As to the malignant parotid neoplasm in female 4(57.14%) and in male3(42.85%). All parotid neoplasm male: female ratio 1:1.3. Two cases involved in deep lobeof parotid & presented with inward and forward bulging of tonsil and pillars. Three cases ofwarthin'stumour only presented with swelling in the tail of parotid gland. In this series outof 30 cases of parotid neoplasm 23 (76.66%) cases were benign and rest 07 (23.33%)were malignant. Pleomorphic adenoma was the most common benign neoplasm 20(66.66%). Mucoepidermoid Carcinoma was most common malignancy 3 (10%) followed byadenoid cystic carcinoma 2 (6.66%). Out of 7, 3 were stage 3(42.85%) and 3 were stage4(42.85%). In histological grading 3 were low grade (42.85%) and 4 were high grade(57.14%). All the patient werepartotidectomy. Few were treated by radical parotidectomyplus radiotherapy.Conclusion: Though it is a small series to comment on the whole spectrum of the parotidgland neoplasm in Bangladesh, yet an idea about the frequency of disease can be establishedbut actual incidence in Bangladesh as a whole can not be ascertained from thisstudy.Journal of Surgical Sciences (2016) Vol. 20 (1) : 7-12